On Minty variational principle for nonsmooth multiobjective optimization problems on Hadamard manifolds - Bhooshan Upadhyay, Balendu; Treanţă, Savin; Mishra, Priyanka (Optimization, 2023)
In this paper, we consider classes of approximate Minty and Stampacchia type vector variational inequalities using Clarke subdifferential on Hadamard manifolds and a class of nonsmooth multiobjective optimization problems. We investigate the relationship between the solution of these approximate vector variational inequalities and the solution of nonsmooth multiobjective optimization problems involving geodesic approximately convex functions. The results presented in this paper extend and generalize some existing results in the literature.